THE EFFECT OF LEADERSHIP STYLE AND MOTIVATION ON THE COVERAGE OF THE COVID-19 VACCINATION MEDIATED BY THE OFFICER PERFORMANCE - Evrilia Trihandayani; P.M Budi Haryono; Wani Devita Gunardi (ID Solutions, 2022)
Vaccination is an effective intervention to break the chain of transmission of COVID-19. The scope of the COVID-19 vaccination is the achievement of the results of the vaccination implementation in accordance with the set targets. Leadership style is the behavior of the leader towards subordinates in achieving the goals that have been set. Motivation of health workers is a condition that gives energy to health workers in encouraging activities, directing and channeling behavior towards achieving needs. The performance of the COVID-19 vaccination officer is a result of work that can be achieved in an effort to achieve the goals carried out based on their duties and responsibilities effectively and efficiently. Objective: to determine the effect of leadership style and motivation of health workers on the coverage of COVID-19 vaccination mediated by the performance of COVID-19 vaccination officers. Methods: this research is descriptive and quantitative analysis, with 129 respondents. Data was collected using a questionnaire and analyzed by Partial Least Square (PLS). Results: leadership style has a positive effect on COVID-19 vaccination coverage, motivation of health workers has a positive effect on COVID-19 vaccination coverage. Leadership style on the performance of COVID-19 vaccination officers has a positive effect. The motivation of health workers on the performance of COVID-19 vaccination officers has a positive effect. The performance of COVID-19 vaccination officers on vaccination coverage had a positive effect. There is a positive indirect effect of leadership style on COVID-19 vaccination coverage through the performance of vaccination officers. And the motivation of health workers towards COVID-19 vaccination coverage through the performance of vaccination officers. From this research we can conclude that leadership style and motivation of health workers can increase the coverage of COVID-19 vaccination through the performance of vaccination officers.